Legal Protection of Secured Creditors in PKPU Homologation: Balancing Collective Debt Restructuring with Individual Creditor Rights - Jonathan Marpaung; Parulian P. Aritonang (Politeknik Siber Cerdika Internasional, 2026)
Background: In insolvency restructuring under PKPU, a fundamental tension exists between the collectivity principle and the protection of secured creditors’ proprietary rights. The Indonesian Insolvency Law lacks explicit mechanisms such as the best-interest-of-creditors test, adequate protection, or differentiated creditor classification, mechanisms proven effective in comparative legal systems (Germany, Netherlands, United States). Objective: This article examines the legal implications of a homologation decision in Suspension of Debt Payment Obligations (PKPU) on separatist creditors who reject a principal debt reduction. Methods: This research uses a doctrinal legal research methodology, focusing on the examination of norms, principles, legislation, and legal doctrines through interpretation and systematic analysis. Results: The analysis focuses on three issues: (1) the juridical legitimacy of including a principal debt haircut in a homologation decision against non-participating separatist creditors; (2) the tension between the principle of collectivity in PKPU and the principle of consensualism in contract law; and (3) a model of balanced legal protection for separatist creditors within the framework of Indonesian insolvency law. The case studies used are the Homologation Decision of PT Bahtera Niaga Indonesia (Number 408/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst) and the Supreme Court Judicial Review Decision Number 10 PK/Pdt.Sus-Pailit/2022. Conclusion: Although a homologation decision is normatively binding on all creditors based on the principle of lex specialis under insolvency law, the application of a haircut to separatist creditors is limited by the best-interest-of-creditors test principle and must not result in the separatist creditor receiving a value lower than the realization value of their collateral.